Analisis Nikel dan Besi pada Bijih Nikel Laterit Menggunakan XRF dengan Metode Pressed Powder dan Pressed Pellet: Analysis of Nickel and Iron in Laterite Nickel Ore Using XRF with Pressed Powder and Pressed Pellet Methods - Rikal, Muh Rival; Gala, Selfina (UIR Press, 2025)
Lateritic nickel ore is the main source of nickel in Indonesia and plays a crucial role in the mining industry. To evaluate ore quality, accurate analysis of nickel (Ni) and iron (Fe) content is required. X-Ray Fluorescence (XRF) is a widely used method because of its rapid and non-destructive nature, as well as its capability to analyze multiple elements simultaneously. However, the analytical results are strongly influenced by the sample preparation method. This study compares two preparation methods, namely pressed powder and pressed pellet, for determining Ni and Fe content in lateritic nickel ore using an Epsilon 4 XRF instrument at PT. Pakubumi Laboratory, North Morowali. The samples were prepared to a size of -200 mesh and tested with varying pressing durations (1, 2, and 3 minutes) for pressed powder and different pressures (20, 25, and 30 PSI) for pressed pellet. The results were statistically processed and compared with Certified Reference Material (CRM) values. The pressed pellet method at 25 PSI produced data closest to the reference values, with an average deviation of less than 1.5% for Ni and 0.2% for Fe across all ore categories. Conversely, the pressed powder method showed higher deviations of about 4–6%, although the 2-minute pressing duration provided slightly better accuracy than other variations. These findings highlight the importance of selecting an appropriate preparation method to ensure the validity of XRF results and recommend the pressed pellet method under optimal pressure as a standard procedure in geochemical analysis of lateritic nickel ore.